Association of caffeine intake with all-cause and cardiovascular mortality in elderly patients with hypertension - Chen, Shuaijie; Li, Jing; Gao, Menghan; Li, Duanbin; Shen, Ruming; Lyu, Lingchun; Shen, Jiayi; Shen, Xiaohua; Fu, Guosheng; Wei, Tiemin; Zhang, Wenbin (Frontiers in Nutrition, 2022)
Background: Caffeine is widely consumed not only in coffee but also in soft drinks and tea. However, the long-term health effects of caffeine are still controversial, especially in people with high cardiovascular risk such as elderly patients with hypertension. Methods: This study analyzed data from the National Health and Nutrition Examination Survey 2003-2018. Caffeine intake was calculated by two 24-hour dietary recall interviews. Complex sampling-weighted multivariable Cox proportional hazards models were used to compare the hazard ratios (HRs) of all-cause and cardiovascular mortality in elderly hypertensive patients with different caffeine intake (<10, 10 to <100, 100 to <200, 200 to <300, ≥300 mg/d). Results: This study included 6076 elderly hypertensive patients. The mean ± standard error follow-up duration was 6.86 ± 0.12 years. During this period, a total of 2200 all-cause deaths occurred, of which 765 were cardiovascular deaths. Taking patients with caffeine intake <10 mg/d as a reference, patients with moderate caffeine intake (200 to <300 mg/d) had a lower risk of all-cause (HR, 0.70 [95% CI, 0.56-0.87]) and cardiovascular (HR, 0.55 [95%CI, 0.39-0.77]) mortality. The benefit of reducing all-cause mortality risk was significant in female patients (HR, 0.65 [95% CI, 0.50-0.85]) or patients with well-controlled blood pressure (HR, 0.63 [95% CI, 0.46-0.87]), but not in male patients or patients with poorly controlled blood pressure. In addition, non-linear relationship analysis also showed that moderate caffeine intake had the lowest HRs of all-cause (Non-linear p =0.022) and cardiovascular mortality (Non-linear p =0.032) in the present study. Conclusion: Moderate caffeine intake is associated with reduced risk of all-cause and cardiovascular mortality in elderly hypertensive patients.